Elementele artei narative în teatrul muzical - Dalu, Felicia (Theatrical Research, 2024)
Elements of Storytelling in Musical Theatre In this paper we have discussed a range of ideas and information that can be obtained from a musical script or score that can help us understand the text intimately as you prepare your role. But how you choose to use this information is a personal matter and will not be the same for any two actors or any two roles. Your job is to put the pieces together, like a detective, in a way that makes sense to you and agrees with the perspective of your particular production. Be careful that what you have done doesn’t simply confirm everything you wanted to feel about a role before you started the investigation. You may also find new information that could lead you to a performance you never would have imagined.